Gut Microbiome Signatures of Risk and Prodromal Markers of Parkinson Disease. Issue 3 (16th July 2021) - Heinzel, Sebastian; Aho, Velma T. E.; Suenkel, Ulrike; von Thaler, Anna‐Katharina; Schulte, Claudia; Deuschle, Christian; Paulin, Lars; Hantunen, Sari; Brockmann, Kathrin; Eschweiler, Gerhard W.; Maetzler, Walter; Berg, Daniela; et al.
Abstract : Objective: Alterations of the gut microbiome in Parkinson disease (PD) have been repeatedly demonstrated. However, little is known about whether such alterations precede disease onset and how they relate to risk and prodromal markers of PD. We investigated associations of these features with gut microbiome composition. Methods: Established risk and prodromal markers of PD as well as factors related to diet/lifestyle, bowel function, and medication were studied in relation to bacterial α‐/β‐diversity, enterotypes, and differential abundance in stool samples of 666 elderly TREND (Tübingen Evaluation of Risk Factors for Early Detection of Neurodegeneration) study participants. Results: Among risk and prodromal markers, physical inactivity, occupational solvent exposure, and constipation showed associations with α‐diversity. Physical inactivity, sex, constipation, possible rapid eye movement sleep behavior disorder (RBD), and smoking were associated with β‐diversity. Subthreshold parkinsonism and physical inactivity showed an interaction effect. Among other factors, age and urate‐lowering medication were associated with α‐ and β‐diversity. Constipation was highest in individuals with the Firmicutes‐enriched enterotype, and physical inactivity was most frequent in the Bacteroides ‐enriched enterotype. Constipation was lowest and subthreshold parkinsonism least frequent in individuals with the Prevotella ‐enriched enterotype. Differentially abundant taxa were linked to constipation, physical inactivity, possible RBD, smoking, and subthreshold parkinsonism. Substantia nigra hyperechogenicity, olfactory loss, depression, orthostatic hypotension, urinary/erectile dysfunction, PD family history, and the prodromal PD probability showed no significant microbiome associations. Interpretation: Several risk and prodromal markers of PD are associated with gut microbiome composition. However, the impact of the gut microbiome on PD risk and potential microbiome‐dependent subtypes in the prodrome of PD need further investigation based on prospective clinical and (multi)omics data in incident PD cases. ANN NEUROL 2021;90:E1–E12